Development of Teaching Materials E-booklet based on Flip PDF Professional on Technological Development in The Period of Perundagian in Indonesia for Students Class X SMK : Pengembangan Bahan Ajar E-booklet berbasis Flip PDF Professional Materi Perkembangan Teknologi pada Masa Perundagian di Indonesia untuk Siswa Kelas X SMK - Vinda Regita Cahyani; Slamet Sujud Purnawan Jati (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
This development research was carried out based on the findings of the potential and problems of learning history at SMK Cendika Bangsa Kepanjen. The availability of various adequate learning facilities, especially in the use of digital technology, allows learning activities to be more innovative and aligned with current developments in technology and information. On the other hand, the lack of availability and development of teaching materials in schools is an important concern because it has an impact on the low value of learning outcomes and has not yet achieved complete learning outcomes. In that regard, the purpose of this research and development is to develop and test the effectiveness of teaching materials e-booklet based on Flip PDF Professional on technological development in the period of perundagian in Indonesia for Students Class X SMK Cendika Bangsa Kepanjen Malang. The research method used is the development research method (R&D) by Sugiyono. Teaching materials e-booklet based Flip PDF Professional are digital teaching materials with a more realistic and attractive appearance because when turning the pages of the e-booklet will move like a real book. The teaching materials contain material text, pictures, videos, maps, and quizzes. The result of calculating the percentage of the material validator is 98.33% and the teaching material validator is 91.66%. Meanwhile, the results of the percentage calculation based on the small group trial were 82.22% and the large group trial was 88.93%. Based on the acquisition of these percentages, teaching materials e-booklet based Flip PDF Professional stated to be very valid and very effective in learning history.